Observational study of changes in dominant ovarian follicle with and without administration of clomiphene citrate in primary infertility cases among eastern Indian women - Susmita Ghosh,; Kausiki Ray Sarkar,; Oyndrila Sengupta,; Subhajit Halder, (Asian Journal of Medical Sciences, 2023)
Background: Changing environment and social factors with advancement of science bestowed the human population with both curse and boon. Increasing number of primary infertility is one of the many challenges which is encountered among 3.59% of Indian women population in reproductive age group. Use of clomiphene citrate (CC) is one of the commonly practiced way to find out a ray of hope. Aims and Objectives: The aim of the study was to measure the changes of morphometric parameters of dominant ovarian follicles and their numbers and compare the same before and after administration of CC was the aim of the present study. Materials and Methods: This interventional and cohort study performed on 50 women coming to the infertility clinic at Institute of Post Graduate Medical Education and Research, Kolkata, with primary infertility of reproductive age group. Informed consent was taken from all. Transvaginal ultrasonography was utilized to measure the parameters related with dominant follicles. Comparison among them with respect to number, size, and time to rupture both before and after ovulation induction with CC was made. Results: Statistically significant increase in number and average size of dominant follicle is seen from 1.08 to 2 and 12.26 to 15.31 mm following CC in the third cycle. In polycystic ovarian disease, cases also ovulation has increased significantly. Conclusion: Transvaginal ultrasonography proves to be regarded as a gold standard procedure to measure and monitor the ovarian follicle status. Undoubtedly CC can be regarded as an easy and dependable solution toward treatment of primary infertility.